(untitled) (Al-Qamar, 2021)
Dr. Zia-ul-Rahman Azmi’s writings in the science of hadith are concerned, "Al-Jami-ul-Kamal" is the most reliable scholarly effort. At the beginning of this book, Sheikh Azmi has written a detailed case called "Al-Mudkhal" which consists of about three hundred pages. Is. You have started this entry with the chain of hadith because the chain of transmission is very important for those who are interested in the science of hadith. The importance of hadith has been clarified by presenting arguments on the Messenger and obedience to the Messenger. Then they mention the Muhaditheen from the first century to the third century with the position and rank of their works. Muhadditheen Sita and other muhaddiths who have collected only authentic hadiths discuss their methods at length, present the reasons for the compilation of Al-Jaami al-Kamal and the method they have chosen in it with great explanation, the hadiths of virtues and commands at the end of the introduction. I also express my opinion while describing the methods of Muhadditheen .